Perceived Herding Behavior and Experienced Regret on Crypto Asset’s Investment Decisions by Millennials - Rosmiwilujeng, Elyza Putri; Satyawan, Made Dudy; Paino, Halil (AKRUAL: JURNAL AKUNTANSI, 2023)
Introduction/Main Objectives: The purpose of this research is to determine the effect of herding behavior and experienced regret on the decision to invest in crypto assets by millennials. Background Problems: The number of crypto asset enthusiasts continues to increase significantly over the past few years. Commodity Futures Trading Supervisory Agency (Bappebti) noted that crypto investors in Indonesia had reached 17.25 million people in April 2023. Novelty: The novelty of this research is explains the differences in crypto asset investment decisions between students and employees. In addition, this research will also explain the crypto asset investment decisions in urban communities in the Surabaya and Sidoarjo areas. Reserach Method: The research method uses a survey method with the research sample consisting of students and employees who are domiciled in urban areas of Surabaya and Sidoarjo. The analysis technique used in this study is multiple linear regression analysis using SPSS version 26 software. Finding/results: The results of the research show that herding behavior and experienced regret have a partial positive effect towards millennials' investment decisions in crypto assets. Conclusion: Therefore, people who live in urban areas such as Surabaya and Sidoarjo are willing to take risks and are open to developments in the investment sector. This can also be shown from the characteristics of research respondents consisting of 48% of crypto asset investors and 52% of capital market investors who are dominated by stocks, where crypto assets and stocks are a type of investment instrument that has a high risk.